2017
DOI: 10.1186/s12936-017-1846-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of Interceptor® G2, a long-lasting insecticide net coated with a mixture of chlorfenapyr and alpha-cypermethrin, against pyrethroid resistant Anopheles gambiae s.l. in Burkina Faso

Abstract: BackgroundMalaria vectors have acquired widespread resistance throughout sub-Saharan Africa to many of the currently used insecticides. Hence, there is an urgent need to develop alternative strategies including the development of new insecticides for effective management of insecticide resistance. To maintain progress against malaria, it is necessary to identify other residual insecticides for mosquito nets. In the present WHOPES phase II analogue study, the utility of chlorfenapyr, a pyrrole class insecticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 31 publications
7
75
1
Order By: Relevance
“…In the hut trials, Interceptor ® G2 and chlorfenapyr nets killed more free-flying mosquitoes (three-fold) relative to standard Interceptor ®. This outcome is similar to that found by N’Guessan et al [ 25 ] in Benin and Bayili et al [ 4 ] in Burkina Faso. This high mortality of resistant malaria vectors is promising for overcoming the threat of resistance in such malaria vector populations.…”
Section: Discussionsupporting
confidence: 92%
“…In the hut trials, Interceptor ® G2 and chlorfenapyr nets killed more free-flying mosquitoes (three-fold) relative to standard Interceptor ®. This outcome is similar to that found by N’Guessan et al [ 25 ] in Benin and Bayili et al [ 4 ] in Burkina Faso. This high mortality of resistant malaria vectors is promising for overcoming the threat of resistance in such malaria vector populations.…”
Section: Discussionsupporting
confidence: 92%
“…This low effect size achieved by MAGNet ® LN against pyrethroid-resistant An. gambiae s.s. mosquitoes is consistent with findings from previous experimental hut trials with pyrethroid-only LLINs performed at the same site [9,26] and elsewhere [7,8,35]. This provides further evidence of the poor performance of pyrethroid LLIN in areas where malaria-vectors have developed multiple mechanisms of pyrethroid resistance [7,36].…”
Section: Discussionsupporting
confidence: 89%
“…Although LLIN may provide some protection against insecticide-resistant Anopheles mosquitoes, this may depend on the frequency and strength of the resistance [7][8][9]. To meet the resistance challenge and restore malaria vector control, new active ingredients are being developed and tested.…”
Section: Introductionmentioning
confidence: 99%
“…However, next generation LLINs either impregnated with pyrethroids and the synergist PBO or containing chlorfenapyr (Interceptor G2 ® ) are potential alternatives for the improved efficacy of LLINs and for resistance management. Several experimental hut studies have shown improved efficacy of PBO and chlorfenapyr LLINs in controlling pyrethroid resistant malaria vectors compared to conventional pyrethroid LLINs [53][54][55][56][57]. LLINs containing PBO or novel insecticide classes should be considered by the NMCP of DR Congo for future LLIN distribution campaigns in areas of moderate to high intensity of pyrethroid resistance, although the costs of these nets would also need to be considered.…”
Section: Discussionmentioning
confidence: 99%